The impact of virtual, remote, and real logistics labs : First international conference, ImViReLL 2012 Bremen, Germany, February 28 - March 1, 2012 Proceedings - Uckelmann, Dieter (Communications in Computer and Information Science, 2012)
This book constitutes the refereed proceedings of the International Conference on the Impact of Virtual, Remote and Real Logistic Labs, ImViReLL 2012, held in Bremen, Germany, in Februar/March 2012. The 16 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on fundamentals and historic background of lab-based research in logistics; infrastructure and design of virtual, remote and real labs; educational implications of virtual, remote and real labs; test-beds and demonstrators; lab-based process improvements in logistics; lab-supported product developments.